The political museum: power, conflict and identity in Cyprus - Stylianou-Lambert, Theopisti; Bounia, Alexandra (My University, 2016)
This engaging volume reveals how politics permeates all facets of museum practice, particularly in regions of political conflict. In these settings, museums can be extraordinarily influential for shaping identity and collective memory and for peace building. Using key Cypriote archaeological, historical, ethnographic, and art museums as examples, this book: provides a multifaceted and deeper understanding of how politics, conflict, national agendas, and individual initiatives can shape museums and their narratives; discusses how these forces contribute to the creation of, and conflict over, national, community and personal identities; examines how museums use inclusion and exclusion in their collections, exhibitions, objects and interpretive material as a way of selectively constructing collective memories. This book will be an important resource for museum professionals, as well as scholars interested in the effects of politics on museums and interpretations of the past.
Keywords: museums; politics; history of museums; Cyprus